Restoring Hair Growth with Individualized Homeopathic Treatment: A Case Report on Alopecia Areata (Advancements in Homeopathic Research, 2025)
Alopecia areata, commonly known as spot baldness,  is a condition where hair loss occurs in small, circular  patches on the scalp or other areas of the body. This  autoimmune disorder affects approximately 1-2% of  the global population and can develop at any age [1].  Typically, it results in coin-sized bald spots on the  scalp, but the condition's course is unpredictable,  leading to various forms such as alopecia totalis,  alopecia universalis, and ophiasis. Although it is an  autoimmune condition, traditional medical treatments  often lead to relapses and come with potential side  effects. This case involved a 15-year-old female  patient who sought treatment at the National Institute  of Homoeopathy (N.I.H) outpatient department  (OPD) for alopecia areata. The patient underwent  individualized homeopathic treatment for seven  months, resulting in a complete recovery without any  adverse effects. Throughout the treatment process, both  the MONARCH score and objective clinical evidence  demonstrated significant improvement, confirming  the effectiveness of homeopathic treatment. The  individualized selection of homeopathic remedies,  based on the totality of the patient's symptoms, proved  to be a valuable approach in achieving successful  outcomes. This case report highlights the potential of  homeopathy in managing alopecia areata, particularly  in cases where conventional treatments may fail to  provide consistent results or cause unwanted side  effects. The positive response observed in this patient  supports the role of homeopathy as a promising  therapeutic option for this challenging condition
Keywords: Alopecia areata; Autoimmune; Homoeopathy; Inflammation; case report